No-wool sheep for Fiji - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In the past Fiji has not had much success in rearing sheep. Wool sheen have failed to perform in the heat but now a specially bred tropical sheep may be set to reverse this trend. The aim of a project by the Ministry of Primary Industries is to...